Evaluation of importance of the expression p53 and bcl-2 genes and Ki-67 cellular proliferation antigen in malignant transformation of the glandular compartment of uterine mucosa - Wlaźlak, Edyta; Surkont, Grzegorz; Suzin, Jacek; Kobos, Józef; Tyliński, Wiesław (Menopause Review/Przegląd Menopauzalny, 2003)
Aim: 1. was to evaluate the distribution of apoptosis-related proteins: P53 and BCL-2 in endometrial carcinoma and in benign proliferate endometrium; 2. to assess the expression of Ki-67 in patients with endometrial carcinoma and with benign proliferate endometrium. Material and methods: 22 cases of endometrial carcinoma and 17 cases of benign proliferation were evaluated with the use of immunohistochemistric methods. The expression of P53, BCL-2 and Ki-67 in glandular component was analyzed. Results: Average value of P53 expression index in proliferate group was noticed as 17.185. In contrast among patients with endometrial carcinoma we found that the average value of P53 expression index was 37.440 (difference statistically significant – p<0.001). Average value of Ki-67 expression index among endometrial carcinoma patients was 59.804. In endometrial proliferative group the value of Ki-67 expression index was calculated at the level of 27.526 (p<0.001). Mean value of BCL-2 expression index in group with endometrial cancer was calculated at the level of 69.824. In proliferative endometrium we noticed that value of BCL-2 expression index was at average 44.448. Differences were not statistically significant (p=0.114). Conclusions: 1. High expression of Ki-67 in glandular component was strongly associated with endometrial carcinoma. 2. In patients with endometrial carcinoma we often detected high expressions of P53 in glandular component. 3. We did not observed statistically significant differences of BCL-2 expression between women with endometrial carcinoma and benign proliferate endometrium in glandular component. 4. We found statistically significant correlation in the degree of the expression of P53 and Ki-67 in glandular component in patients with endometrial carcinoma.